Chemical profile, botanical origin, and antioxidant activity of stingless bees propolis from Konawe Island, Southeast Sulawesi, Indonesia - NIKEN PUJIRAHAYU; ZAKIAH USLINAWATY; HALIMAHTUSSADDIYAH RITONGA; NURHAYATI HADJAR; DINI PRASETYA; DIRVIN DIRVIN; AHMAT GARI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Pujirahayu N, Uslinawaty Z, Ritonga H, Hadjar N, Prasetya D, Dirvin, Gari A. 2025. Chemical profile, botanical origin, and antioxidant activity of stingless bees propolis from Konawe Island, Southeast Sulawesi, Indonesia. Biodiversitas 26: 2495-2507. This study aimed to determine the chemical profile, plant sources, and antioxidant activity of stingless bee propolis from Konawe Islands Regency, Southeast Sulawesi, Indonesia. Gas Chromatography-Mas Spectrometry (GC-MS) was used to determine the chemical composition of propolis. The antioxidant activity of propolis ethanol extract was then tested using the DPPH method. The results showed that 2 species of stingless bees, Tetragonula aff. biroi and Tetragonula sapiens exhibited chemical compounds with similarities and differences. These compounds consisted of triterpenes and diterpenes, such as 9,19-cyclolanost-24-en-3-ol, (3?.), 9,19-cyclolanost-24-en-3-ol acetate, lupenone, solanesol, norolean-12-ene, beta-amyrone, methyl commate b, ergosta-8,24(28)-dien-3-ol, 4,14-dimethyl-,(3?.,4?,5?), ?-amyrenone, and tricyclo[20.8.0.0(7,16)] triacontane, 1(22),7(16)-diepoxy. Others included phenolics, such as 3-[pentadecylphenol and 5-heptylresorcinol. A comparison of GC-MS analysis of propolis extract and plant exudates showed that the botanical origin of propolis was Anacardium occidentale (cashew), Mangifera indica (mango), and Artocarpus heterophyllus (jackfruit). Propolis ethanol extract from T. aff. biroi and T. sapiens had strong antioxidant activity with IC50 of 96.8 4±2.35 µg/mL and 49.5±0.42 µg/mL, respectively. Based on the results, the extract from two species of bees could be a potential source of antioxidant agents as medicinal ingredients and immune supplements in the food and pharmaceutical industry.